2021
DOI: 10.1080/19490976.2021.1927634
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pig farming on human Gut Microbiota: role of airborne microbial communities

Abstract: It has been hypothesized that both genetics and diet influence the composition of the human cecal microbiota. However, it remains unclear whether and how occupational exposure to microbes impacts the microbial communities in human guts. Using a One Health approach, we visited pig farms (n = 26) and collected stool specimens from pig workers (n = 59), pig barn air samples (n = 19), and rectal swabs from pigs at three different growth stages (n = 144). Stool samples from cattle workers were included as a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(50 reference statements)
2
18
1
Order By: Relevance
“…shown that the gut microbiome of farmworkers and those in close contact with livestock is altered compared to controls without such contact [88,89]. Our results, without controls, could not assess the origin of these similarities, but instead provided a snapshot of the status of human and chicken microbiomes in this environment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…shown that the gut microbiome of farmworkers and those in close contact with livestock is altered compared to controls without such contact [88,89]. Our results, without controls, could not assess the origin of these similarities, but instead provided a snapshot of the status of human and chicken microbiomes in this environment.…”
Section: Discussionmentioning
confidence: 73%
“…When we looked on a finer scale at individual microbes and ARGs, we observed that 14% of species and 76% of ARGs found in humans were also present in chickens. Case-control studies have shown that the gut microbiome of farmworkers and those in close contact with livestock is altered compared to controls without such contact [ 88 , 89 ]. Our results, without controls, could not assess the origin of these similarities, but instead provided a snapshot of the status of human and chicken microbiomes in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ASVs identified using DADA2, we calculated the alpha-diversity values for Shannon diversity indices using the estimate_richness command in the phyloseq package (version 1.32.0) in R. The alpha-diversity values for the sample types (farm and SPF pigs) were calculated and analyzed statistically using Wilcoxon rank-sum tests (using the wilcox.test function in R). Distance matrices were calculated for the beta-diversity analyses and used as input files for the non-metric multidimensional scaling (NMDS) plots as described [ 48 ]. Statistical analysis was performed by permutation test (PERMANOVA; Adonis function).…”
Section: Methodsmentioning
confidence: 99%
“…tests (using the wilcox.test function in R). Distance matrices were calculated for the beta-diversity analyses and used as input files for the non-metric multidimensional scaling (NMDS) plots as described [48]. Statistical analysis was performed by permutation test (PERMANOVA; Adonis function).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Based on the ASVs identified using DADA2, we calculated the alpha-diversity values for Shannon diversity indices using the estimate_richness command in the phyloseq package (version 1.32.0) in R. The alpha-diversity values for the sample types (farm and SPF pigs) were calculated and analyzed statistically using Wilcoxon rank-sum tests (using the wilcox.test function in R). Distance matrices were calculated for the beta-diversity analyses and used as input files for the non-metric multidimensional scaling (NMDS) plots as described (Moor et al, 2021). Statistical analysis was performed by permutation test (PERMANOVA; Adonis function).…”
Section: Methodsmentioning
confidence: 99%